The institutional approach in the study of the political system ( Turkish military institution as a model) - Babela, Dlshad M. (Humanities Journal of University of Zakho, 2013)
The institutional approache is one of the oldest approaches used in the study of analysis political systems; it was limited as traditional study of formal institutions of the state, legislative, executive and judiciary institutions, as well as the state constitution. The concern on this approach was diminished in the fifties and sixties of the twentieth century as a result of appearance entries such as structural functional and behavioral direction, But the appearance of new institutional in seventies of twentieth century brought a new attention of researchers to use of this approach, with non-possibility of Indispensable it completely, and because it cast light on the important aspects within political systems. And During this research we want to focus light on theTurkish military model as an introduction to the study and analysis of theTurkish political system through the statement of this institution role and position within the Turkish state and their relationship with civil authority of the government institution. This study shows that The military institution has the prominent location within the institutional pyramid in the Turkish political system, despite that this role has been Affected after the reception of ( The Justice and Development Party) came to power in Turkey, and its moving relatively away from the Turkish political stage, However, the survival of a lot of props which previously relied on in its interventions in policymake the possibility of her return-entry to this role possible, especially in the case of failure of (Justice and Development Party) in achieving its political program which is considered curtail the role of the military and civilian control of the military institution as one of the most important terms of this program. The Study hypothesis runs from consideration the institutional approach as anecessary approach in the study of political systems where cast light on important aspects of the work of the political system and the Turkish military considered values applied Model to analyze the​​ Turkish political system on its light. And we divide study into two parts: The first part focuses on the institutional approach in analysis of the political system, and The second part, cast light on Turkish military before and after the establishment of Republic.